Control of Methicillin-Resistant Staphylococcus aureus Using Photodynamic Therapy in Synergy with Staphylococcus epidermidis: Role of Mixed Cultures in Developing Strategies to Inhibit Infections - Rebeca Vieira de Lima; Kate Cristina Blanco; Vanderlei Salvador Bagnato (Microorganisms)
Staphylococcus aureus is a Gram-positive bacterium living abundantly on our skin and mucous membranes. When there is an imbalance in microbiota, they are the main protagonists of various infections, such as soft tissue infections and bacteremia. However, Staphylococcus epidermidis also colonizes this microbiome, is able to compete with pathogenic bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), and can contribute to treatments such as photodynamic inactivation (PDI) by inhibiting infection progression and restoring a healthy microbiota. In vitro photodynamic inactivation experiments were carried out using synthetic curcumin at a concentration of 5 μM as a photosensitizer and varying light doses (1, 2 and 5 J/cm2) at a wavelength of 450 nm, on pure cultures (S. aureus, S. epidermidis and MRSA) and mixed cultures, in which bacteria were placed together proportionally. This study revealed that pure cultures of these bacteria obtained statistically significant results with varying light doses of 2 and 5 J/cm2. In addition, in an attempt to bring infections closer to reality, experiments were carried out on mixed cultures. The results were not only significant but also increased reduction of bacteria, including resistant bacteria. Study offers new perspectives on the importance of themicrobiota for treatment of infections caused by the Staphylococcus genus.